2020
DOI: 10.3389/fmicb.2020.00714
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Gut Microbiota and Metabolite Profiles Induced by Different Feeding Methods in Healthy Chinese Infants

Abstract: Human milk is closely correlated with infant gut microbiota and is important for infant development. However, most infants receive exclusively insufficient breast milk, and the discordance between effects of commercial formula and human milk exists. To elucidate the differences induced by various feeding methods, we determined microbiota and metabolites composition in fecal samples from 77 healthy infants in Northeast China and identified the differences in various feeding methods. Bacterial 16S rRNA gene sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 68 publications
7
53
1
Order By: Relevance
“… 16 However, substantial differences have been found between the gut microbiota composition of formula-fed and breastfed infants. 16 , 35 Those differences are due in part to the low concentrations and different structures of oligosaccharides found in infant formulas compared to human milk. 15 Infant formulas are based in bovine milk, which does not contain type-1 oligosaccharides, 15 lacking therefore the predominant LNB structural unit of HMOs.…”
Section: Discussionmentioning
confidence: 99%
“… 16 However, substantial differences have been found between the gut microbiota composition of formula-fed and breastfed infants. 16 , 35 Those differences are due in part to the low concentrations and different structures of oligosaccharides found in infant formulas compared to human milk. 15 Infant formulas are based in bovine milk, which does not contain type-1 oligosaccharides, 15 lacking therefore the predominant LNB structural unit of HMOs.…”
Section: Discussionmentioning
confidence: 99%
“…In the mixed-fed group they detected increased levels of cis-11,14-eicosadienoic acid, stearidonic acid, capric acid, myristic acid, docosahexaenoic acid, cis-8,11,14-eicosatrienoic acid, and 15-oxoete. Interestingly, only eicosapentaenoic acid was elevated in stool samples of the exclusive formula-fed group (Li et al, 2020). Varying results of fecal fatty acid profiles between different studies could be due to the variable fatty acid composition of different infant formulas.…”
Section: Increased Fatty Acids In Breastfed Children Reflected Fatty Acid Composition Of Breast Milkmentioning
confidence: 93%
“…On the contrary, a different study reported myristic acid to be significantly higher in formula-fed infants (Chow et al, 2014). Li et al observed a series of different fatty acids, significantly altered in fecal samples of breastfed, mixed-fed, exclusively formula-fed or complementary food-fed infants (Li et al, 2020). In the mixed-fed group they detected increased levels of cis-11,14-eicosadienoic acid, stearidonic acid, capric acid, myristic acid, docosahexaenoic acid, cis-8,11,14-eicosatrienoic acid, and 15-oxoete.…”
Section: Increased Fatty Acids In Breastfed Children Reflected Fatty Acid Composition Of Breast Milkmentioning
confidence: 95%
See 1 more Smart Citation
“…Purified amplicons were pooled in equimolar and paired-end sequenced (2 × 250) on an Illumina platform. The details of DNA extraction, PCR amplification, quantitative PCR, amplicons purification, sequencing, and high-quality sequences criteria are those described by Li ( Li et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%